Secure dynamic source routing protocol for defending black hole attacks in mobile Ad hoc networks - M. Mohanapriya; Nitish Joshi; Mohit Soni (Institute of Advanced Engineering and Science, 2021)
Wireless Ad Hoc Network is a dynamically organized network on emergency situations, in which a group of wireless devices send data among themselves without requiring any base stations for forwarding data. Here the nodes itself perform the functions of routing. This important characteristic of mobile ad hoc networks allows the hassle free set up of the network for communications in different crisis such as battlefield and natural disaster zones. Multi hop communication in MANET is achieved by the cooperation of nodes in forwarding data packets. This feature of MANET is largely exploited to launch a security attack called black hole attack. A light weight solution called SEC-DSR is proposed to defend the network from black hole attack and enables communication among nodes even in the presence of attackers. In this scheme, by analyzing only the control packets used for routing in the network, the compromised nodes launching the attack are identified. From the collective judgment by the participating nodes in the routing path, a secure route free of black hole nodes is selected for communication by the host. Simulation results validate and ensure the effectiveness of the proposed solution tested on an ad hoc network with compromised black hole nodes.